Is first-line treatment with polatuzumab vedotin–rituximab–cyclophosphamide, doxorubicin and prednisone (pola-R-CHP) for previously untreated diffuse large B-cell lymphoma cost-effective in China? A cost-effectiveness analysis using a Markov model - Lin Yang; Ting Chen; Qiuling Zhao; Liangliang Dong; Wanfu Zhong; Wenbin Liu; Xiuliang Qiu; Ruyi Huang; Shengqiang Huang; Ruixiang Xie (BMJ Open)
Objective To evaluate the cost-effectiveness of polatuzumab vedotin–rituximab–cyclophosphamide, doxorubicin and prednisone (pola-R-CHP) in CD20-positive patients with previously untreated diffuse large B-cell lymphoma (DLBCL) in China.Design A Markov model was constructed to analyse the cost-effectiveness of two strategies in CD20-positive patients with previously untreated DLBCL over a lifetime horizon: (1) pola-R-CHP and (2) rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP). The clinical outcomes were obtained from the POLARIX(NCT03274492), SCHOLAR-1, ZUMA-7(NCT03391466) and TRANSFORM(NCT03575351) trials. Costs were derived from the Chinese official websites and published literature, and utility values were obtained from the published literature. The willingness-to-pay (WTP) threshold was set at triple the 2023 Chinese per capita gross domestic product of US$38 042.49/quality-adjusted life year (QALY). Uncertainty was addressed using sensitivity analyses. The scenario analyses were also conducted.Setting Chinese healthcare system perspective.Participants A hypothetical cohort of adult patients presenting with CD20-positive, patients with previously untreated DLBCL.Interventions Pola-R-CHP versus R-CHOP.Main outcome measures The main outcomes of the study were QALYs, incremental cost-effectiveness ratio (ICER) and incremental net-health benefit (INHB).Results In China, the ICER and INHB of pola-R-CHP compared with R-CHOP were US$77 036.33/QALY and −1.11 QALYs, respectively. The ICER was above the WTP threshold. Outcomes were most responsive to the price of pola. Probabilistic sensitivity analyses indicated that pola-R-CHP had a low probability of being cost-effective under the current WTP threshold. The scenario analyses demonstrated that when the price of pola fell by more than 32.5% to less than US$33.19/mg, the economic probability of pola-R-CHP was greater than 50% in previously untreated CD20-positive patients with DLBCL in China.Conclusions Pola-R-CHP is not cost-effective in the first-line treatment for previously untreated CD20-positive DLBCL in China. A value-based price for the cost of pola is less than US$33.19/mg.